(3GJLGgGJ EOGQI GdeYdheGJ (B/s - (3GdYGeQj, GSGeIs ((3YeGf(B: s (3OGQ GSGeI(B, s, 2009)
(3eaGgje h CSGdjH h fXQjGJ GdGOGQI , eMJhi h eVehf eUGOQ GdeYdheGJ h GfhGYgG , GdeYdheGJ h OhQgG aj GOGQI GdHMhK GdYedjI , GOGQI GdeYdheGJ , GdNOeGJ GdeYdheGJ aj eQGcR GdeYdheGJ GdeJNUU , GYOGO Gdbhi GdYGedI dLeY GdeYdheGJ , GdGJUGd GdGOGQj aj GdeYdheGJ GdOGNdjI h GdNGQLjI , GdGJLGJ GdeSJbHdjI dCTcGd eUGOQ GdeYdheGJ , GdHjGfGJ , OhQ GdJShjb aj JWhjQ NOeGJ GdeYdheGJ , GdhSGFW aGFbI GdJOGNd (B( (3GdgjHQejOjG (B) (3h eSJbHd GdhUhd ddeYdheGJs
(3eQGLY U(B.213s
Keywords: (3GdeYdheGJs; (3fXe GdeYdheGJ `` GOGQIs